The Concept of Islamic Education in Salafi Understanding of Politics - Nuha Putri Rahmawati; Mohammad Zakki Azani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Salafi political thought is one of the important studies in contemporary Islam that has an influence on various aspects of Muslim life, including Islamic education. Salafism as an understanding that seeks to restore the teachings of Islam to the practice of the salaf generation not only emphasizes aspects of faith and worship, but also includes social and political dimensions. In its development, the political thought of the Salafis shows a diversity of views, ranging from the attitude of staying away from politics, being passive and obeying the legitimate government, to active involvement in Islamic education as seen in the cultivation of the value of obedience to leaders, strengthening the faith, social stability, and the formation of students' character. Islamic political values are transformed through curriculum, learning methods and the example of educators that emphasize the habituation of amar ma'ruf nahi munkar. Islamic education in the Salafi perspective is not only directed at intellectual development, but also the development of moral, spiritual and social responsibility of students as servants of Allah and citizens. Therefore, Salafi political thought contributes to strengthening the values of Islamic education which is oriented towards the formation of character and religious awareness in the life of society and the state.